2022
DOI: 10.1038/s41598-022-08593-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colloidal and pseudo-colloidal transport of actinides in nitrate contaminated groundwater near a radioactive waste repository after bioremediation

Abstract: The possible role of biogeochemical processes in the transport of colloidal and pseudo-colloidal U, Np, and Pu during bioremediation of radionuclide- and nitrate-contaminated groundwater was investigated. In two laboratory experiments with water samples taken from contaminated aquifers before and post bioremediation, we found that microbial processes could cause clayed, ferruginous, and actinide colloids to coagulate. The main mechanisms are biogenic insoluble ferrous iron species formations (goethite, pyrrhot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…The question of their transport processes under geochemical conditions and their interaction with the surroundings is also of particular interest. 47,48 This assertion is strengthened by the reported high physical and chemical stability of Pu colloids even when increasing the ionic strength. [49][50][51] Focusing on the structure, recent studies have demonstrated that intrinsic colloids exhibit a PuO 2 -like structure differing from their bulk counterparts in terms of local environment, structural disorder and a possible contribution of different oxidation states in the oxide.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The question of their transport processes under geochemical conditions and their interaction with the surroundings is also of particular interest. 47,48 This assertion is strengthened by the reported high physical and chemical stability of Pu colloids even when increasing the ionic strength. [49][50][51] Focusing on the structure, recent studies have demonstrated that intrinsic colloids exhibit a PuO 2 -like structure differing from their bulk counterparts in terms of local environment, structural disorder and a possible contribution of different oxidation states in the oxide.…”
Section: Introductionmentioning
confidence: 98%
“…The question of their transport processes under geochemical conditions and their interaction with the surroundings is also of particular interest. 47,48 This assertion is strengthened by the reported high physical and chemical stability of Pu colloids even when increasing the ionic strength. 49–51…”
Section: Introductionmentioning
confidence: 99%
“…In the case of open-type radioactive waste storage basins, besides nitrates and sulfates, the migration of soluble forms of long-lived radionuclides, such as actinides (U, Np, Pu, and Am) and fission products (Cl, Cs, Se, Sr, and Tc), into groundwater poses a greater risk. It is important to note that the solubility and the migration ability of many elements in higher oxidation states (U, Np, Pu, Se, and Tc) increase in the presence of nitrate and carbonate ions, certain organic complexing agents, iron-bearing clay, and organic colloidal particles [11][12][13][14][15][16][17]. The distribution of radioactive and chemical pollutants in groundwater, in addition to their chemical properties, depends on the porosity of aquifers, the mineral composition of surrounding rocks, and the characteristics of hydrodynamic regimes within aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Some soluble substrates could lead to the desorption of actinides from rocks due to soluble complex formation. In our previous work, it was determined that bioremediation could reduce the risk of colloidal and pseudocolloidal transport of actinides through the aggregation of colloids by microbial metabolites during in situ bioremediation of groundwater near the B2 storage facility at the Siberian Chemical Combine [12]. In this case, milk whey, sugar, and acetate were all used in laboratory and field experiments.…”
Section: Introductionmentioning
confidence: 99%
“…또한 많은 연구 결과에 의 하면 철질(ferruginous), 점토질, 유기물 콜로이드의 지하 수 내 이동은 우라늄이 지하에서 이동하는데 중요한 역할 을 한다(Smith and Degueldre, 1993;McCarthy et al, 1998;Kurosawa and Ueta, 2001;Novikov et al, 2006). 방사성핵종과 질산이온으로 오염된 지하수 내에서 콜로 이드와 pseudo-colloid의 이동 중 생지구화학적 과정의 역 할에 대한 실험실적 연구가 수행된 바 있다(Safonov et al, 2022). 오염 지하수 시료에 대하여 미생물학적 환원 처리 전과 후를 비교한 결과, 처리 후에 용존 우라늄 함량은 10배 이상, 플루토늄 함량은 검출한계 이하로 감소하였다.…”
unclassified